A critical analysis of legal and policy responses to the COVID-19 pandemic and its long-term impacts in Taiwan - Wu, Hsing-Hao; Chen, Chih Wei (Penerbit Universiti Kebangsaan Malaysia, 2021)
The COVID-19 pandemic has dramatically impacted public health and economic and social stability worldwide since the WHO’s Public Health Emergency of International Concerns declaration in early March 2020. The COVID-19 virus was first discovered in December 2019 in Wuhan city, China, and eventually resulted in the global pandemic, of which the cumulative cases have reached 181,367,824 at the time of writing. Taiwan encountered severe public health threats because of the frequent travelers as many as 10 million who commuted annually between mainland China and Taiwan. Recognizing the imminent threats arising from an intensive flow of people from mainland China due to the lockdown policy adopted by the Chinese government, Taiwan has adopted strict border control, sophisticated contact tracing and monitoring measures, and most importantly the securing of sufficient Personal Protection Equipment supply for citizens to prevent community spread. Taiwan’s quick and precise COVID-19 response at the early stage of containing the virus has been proven very successful since the outbreak of the COVID-19 global pandemic in late February 2020. Taiwan is now struggling to fight the recent outbreak for lacking sufficient vaccines and testing capacities and shall learn from other country’s experience for countermeasures against a massive epidemic. This article aims to explore the key elements for the early success of containing the COVID-19 virus, including the comprehensive legal framework for preventing infectious disease, highly trained public health officials and governance system, and citizen self-awareness. The article then discusses the potential legal controversies and their long-term impacts on Taiwan. Finally, this article provides the concluding observation and suggestions for fighting massive infectious diseases.